Analisis Radius Persebaran (Dispersi) Karbon Monoksida Di Jalan Raya Darmo Kota Surabaya - Ananda Iqbal Ibrahim; Firra Rosariawari (Faculty of Engineering, Universitas Serambi Mekkah, 2024)
In this research, the concentration of carbon monoxide (CO) on Jalan Raya Darmo, Surabaya City, which is one of the main highways with heavy traffic, was measured and analyzed. The main aim of this research is to measure CO concentrations and create practical plans to reduce pollution levels. The process consists of collecting information about CO concentration, wind speed, temperature, and air humidity using instruments including hygrometers, anemometers, and CO analyzers. The CO distribution was modeled using the AERMOD dispersion model according to the collected data and the associated meteorological conditions. The research findings revealed that CO concentrations varied significantly depending on traffic volume and weather, with the highest figure being 13,704 μg/m3 on Friday afternoon and the lowest figure being 5,224 μg/m3 on Monday morning. A strong CO distribution pattern was found towards the North, Northeast, West and Southwest using AERMOD for distribution analysis. The research conclusion proves that the amount of CO on Jalan Raya Darmo is significantly influenced by weather and traffic density. It is recommended that risk management techniques be used, such as routine motor vehicle maintenance, implementation of odd-even programs, and regular air quality audits to manage and reduce air pollution.